Realization of Raman amplifier with reverse multi - wavelength pumping - WANG Hui; WEI Dun-kai; SHEN Jun; JIANG Feng-xian (Tongxin xuebao)
A fiber Raman amplifier with bandwidth of 90 nm using eight pump lasers was presented. Based on the theoretic model, a gain of （11.5±1） dB was obtained with the 25 km SMF manufactured by Corning Corp as gain media. The experimentally measured spectra of signal gain coefficient and inter-pump gain coefficient for different pump parameters are in good agreement with the results of improved theoretic model.